ANALISIS MANAJEMEN PEMELIHARAAN TERNAK SAPI BALI DI DESA LENANGGUAR KECAMATAN LENANGGUAR - Zulfy Ramdani, Muhammad; Budiman, Cecep; Hamdani, Asrul; Sudirman, Sudirman; Yani, Ahmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Bali cattle farming is one of the strategic livestock sectors that contributes significantly to rural livelihoods and regional economic development in Sumbawa Regency. However, cattle productivity remains relatively low due to traditional management practices, limited feed resources, and inadequate implementation of livestock management principles. This study aimed to analyze the management practices of Bali cattle farming in Lenangguar Village, Lenangguar District, Sumbawa Regency. The study employed a descriptive qualitative approach. Data were collected through interviews, observation, and documentation involving 50 cattle farmers selected using proportional random sampling. The results revealed that most farmers were in productive age groups and primarily worked as crop farmers. The management system applied by farmers was generally traditional to semi-intensive. Natural grazing areas and agricultural by-products were the main sources of feed. The implementation of livestock management aspects, including breeding, feeding, housing, health management, and disease prevention, was categorized as moderate. Limited educational background and dependence on natural resources were identified as major constraints in improving livestock productivity. Therefore, strengthening extension services, improving feed management, and enhancing livestock health programs are necessary to support sustainable Bali cattle development in Lenangguar Village.